2014
DOI: 10.4236/aar.2014.35048
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy: Prevalence among Elderly Care Givers and Its Impact on the Frequency of Elderly Hospitalization and Elderly Health Related Quality of Life

Abstract: Caring for the elderly is an extremely lonely and frustrating vigil. The care giver has the responsibility of caring for an elderly one to the myriad decisions on different topics such as diabetes care or cancer treatment. Care givers with low levels of health literacy have less health knowledge, worse management of chronic disease and lower use of preventive services. This study was conducted to determine the prevalence of health literacy among elderly care givers and its impact on the frequency of elderly ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
2
4
1
Order By: Relevance
“…In distinction to prior reports from the MENA region ( Almaleh et al, 2017 ; Bener & Ghuloum, 2011 ; Rahman, 2014 ), we found that sex was not a significant predictor of health literacy. This was more in line with findings from Europe and the United States ( HLS-EU Consortium, 2012 ; Rikard et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In distinction to prior reports from the MENA region ( Almaleh et al, 2017 ; Bener & Ghuloum, 2011 ; Rahman, 2014 ), we found that sex was not a significant predictor of health literacy. This was more in line with findings from Europe and the United States ( HLS-EU Consortium, 2012 ; Rikard et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This disagrees with Awad, S., et al, 2019 it was observed that less than two third two thirds of the study participants lived with their spouses. This agrees with Abd El-Rahman, 2014 [3] . Who reported that 46% of the participants were married and lived with their husbands.…”
Section: Discussionsupporting
confidence: 91%
“…But this agree with Fahad et al, 2015 [8] . it was found that more than half of the studied participants had low level of health literacy, and this is similar to results reported by Abd-El Rahman, 2014 [3] . it was found that three quarters of the studied sample had low health literacy.…”
Section: Discussionsupporting
confidence: 90%
“…Caregiver HL seems to have a direct effect on the number of hospitalizations, the hospital length of stay, as well as on the number of accesses to the emergency room of the assisted people, and the resulting costs [ 12 , 13 ]. In fact, a low level of caregivers’ HL is associated with greater difficulty in interpreting medical prescriptions, reduced adherence to therapy and healthy behaviors, inability to recognize adverse drug reactions and possible therapeutic failures [ 14 ].…”
Section: Introductionmentioning
confidence: 99%